2012
DOI: 10.1007/bf03404070
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Diabetes in British Columbia and Quebec: Prevalence and Health Service Utilization

Abstract: he number of people with type 2 diabetes is increasing and has become a global health priority. It is estimated that the prevalence of diabetes for all age groups worldwide will increase from 2.8% in 2000 to 4.4% in 2030. 1 Diabetes can lead to complications such as blindness, renal disease, cardiovascular diseases, amputations, and premature death. It is a significant economic burden in both developing and developed countries. 2 Studies from several countries have shown that immigrants have higher rates of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Although they reported differences in socio‐demographic risks factors, such as older age and less educational attainment in those with language barriers, they found no differences in the rates of diabetes complications. The similarity in the rates of diabetes related complications between English and non‐English speaking individuals can be explained by; 1) non‐English speaking adults readily access primary care services; 2) improved communication with family members and hospital based interpreter services; 3) translated educational materials and the increase in community support groups …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although they reported differences in socio‐demographic risks factors, such as older age and less educational attainment in those with language barriers, they found no differences in the rates of diabetes complications. The similarity in the rates of diabetes related complications between English and non‐English speaking individuals can be explained by; 1) non‐English speaking adults readily access primary care services; 2) improved communication with family members and hospital based interpreter services; 3) translated educational materials and the increase in community support groups …”
Section: Discussionsupporting
confidence: 85%
“…The similarity in the rates of diabetes related complications between English and non-English speaking individuals can be explained by; 1) non-English speaking adults readily access primary care services; 2) improved communication with family members and hospital based interpreter services; 3) translated educational materials and the increase in community support groups. [12][13][14] We found that more than two-thirds of patients with DR had poor diabetes control in both the EDMP and NEDMP. Similar findings from our work also reflect these unsatisfactory levels of diabetes control in English speaking adults.…”
Section: Discussionmentioning
confidence: 71%
“…The effect of measures of socioeconomic status like income and education on health-care access and utilization could apply to all ethnic groups and to both immigrants and nonimmigrants. However, in Canada, factors like unemployment and low occupational status, and language proficiency could be more relevant to immigrants (Dean and Wilson 2009;Wang et al 2012;Wu et al 2005). Low official language proficiency is especially applicable for immigrants from countries where neither English nor French are used widely.…”
Section: Immigration Ethnicity and Health-care Access And Utilizationmentioning
confidence: 99%
“…The Tokelau Island Migrant study was among the first to demonstrate that the incidence of T2D was higher in migrants to New Zealand than in those remaining in their homeland . Studies from many parts of the world have since shown that the prevalence of diabetes is high in migrants . Migration involves losses, disruption to usual life habits, exposure to new experiences and challenges that can impact adiposity and T2D through nutrition transition to high‐caloric diets, physical inactivity, stress and neighbourhood deprivation .…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies from many parts of the world have since shown that the prevalence of diabetes is high in migrants. [17][18][19][20] Migration involves losses, disruption to usual life habits, exposure to new experiences and challenges that can impact adiposity and T2D through nutrition transition to high-caloric diets, physical inactivity, stress and neighbourhood deprivation. 21,22 Pacific people (40%), M aori (27%) and Asian (20%) people are more likely to reside in the poorest areas (NZ Dep 13 Quintile 5 areas) than people of European descent.…”
Section: Figurementioning
confidence: 99%